Evaluation of eight melanocytic and neural crest‐associated markers in a well‐characterised series of 124 malignant peripheral nerve sheath tumours (MPNST): useful to distinguish MPNST from melanoma?. Issue 6 (23rd October 2018) - Gaspard, Margot; Lamant, Laurence; Tournier, Emilie; Valentin, Thibaud; Rochaix, Philippe; Terrier, Philippe; Ranchere‐Vince, Dominique; Coindre, Jean‐Michel; Filleron, Thomas; Le Guellec, Sophie
Abstract : Aims: The diagnosis of malignant peripheral nerve sheath tumour (MPNST) may be challenging, especially in the sporadic setting. Owing to the lack of specific histological criteria, immunohistochemical and molecular diagnostic markers, several differential diagnoses must be considered, especially melanoma. Indeed, although S100 protein usually stains melanoma, other melanocytic markers are often negative, especially in spindle cell/desmoplastic types. This pattern of immunoreactivity resembles that of some nerve‐derived tumours such as MPNST. Owing to their different clinical behaviours and therapeutic implications, accurate identification of these two different tumours is crucial. Methods and results: S100, SOX10, KBA62, MITF, HMB45, Melan‐A, tyrosinase PNL2 and BRAF‐V600E immunostaining was performed in a pathologically and genetically well‐characterised cohort of primary MPNST ( n  = 124), including 66 (53%) NF1‐associated tumours. Sox10 and KBA62 expression were found, respectively, in 102 (84%) and in 101 (83%) MPNST, whereas S100 was expressed in 64 cases (52%). We observed an increased loss of S100 with increasing histological grade ( P  = 0.0052). We found Melan‐A expression in 14% ( n  = 17) of all MPNST, occurring in 82% ( n  = 14) of cases in an NF1 context. Six per cent ( n  = 8) of MPNST showed tyrosinase positivity, including seven (87%) NF1‐associated. MITF expression was found in 10 (8%) MPNST. None expressed PNL2, HMB45 or BRAF‐V600E. Conclusion: MPNST (in NF1 and a sporadic setting) can quite often be positive for Melan‐A, tyrosinase and MITF. Pathologists should be cognisant of these exceptions to prevent confusion with melanoma.